The obtaining and properties investigation of plasma formation at pulse discharge in water aerosol - Iukhymenko, V.V.; Fedirchyk, I.I.; Chernyak, V.Ya.; Martysh, E.V.; Fedorovich, O.A.; Lisitchenko, T.E.; Belenok, N.V. (Вопросы атомной науки и техники, 2013)
The results of investigation of electro-physical and spectral properties of the impulse discharge plasma in aerosol were represented in work. The discharge current, voltage and integral spectrum of plasma were measured. The discharge space was filmed with the help of digital camera. The plasmoids with lifetimes about 150 milliseconds in the autonomous stage after current zero were observed. Представлены результаты исследования электрофизических и спектральных свойств плазмы импульсного разряда в аэрозоле. Были измерены ток разряда, напряжение и интегральный спектр плазмы. Область разряда наблюдалась с помощью цифровой камеры. Наблюдалось появление плазмоидов с временем жизни порядка 150 мс в автономном режиме (после прекращения тока разряда). Представлені результати дослідження електрофізичних та спектральних властивостей плазми імпульсного розряду в аерозолі. Були виміряні струм розряду, напруга та інтегральний спектр плазми. Область розряду спостерігалась з допомогою цифрової камери. Спостерігалась поява плазмоїдів з часом життя близько 150 мс в автономному режимі (після припинення струму розряду).